Modelo de planificación balanceado y modelo de asignación - Oviedo, Jorge; Rubio, Ana (Estudios de Economía, 2016)
Baïou y Balinski (2002) generalized the model of firms-workers allocation to one in which allocation is planned determining both the allocation of workers to firms and how much time workers will dedicate to firms. A planning is stable if there is no pair of firm- worker that could increase their hours of work together, affecting some less desirable agent. This article studies the relationship between this problem and a matching problem, and shows that each stable planning is equivalent to some stable matching.